Afterword: Structural unity? - J-A. van den Berg (Acta Theologica)
From text: The foregoing research design was presented on the basis of associative networks of meaning derived from the metaphor of architecture. By making use of concepts associated with this metaphor, the domain for the interdisciplinary dialogue between practical theology and future studies was traced out from the very first page.